Strategi Komunikasi Bimbingan Masyarakat Islam Dalam Konseling Pranikah Sebagai Terapi Bagi Calon Pengantin - Saraswati Sidiq; Zikri Fachrul Nurhadi; R. Ismira Febrina (Alhadharah: Jurnal Ilmu Dakwah, 2024)
Pre-marital guidance plays a pivotal role as the initial gateway to fostering a harmonious marriage characterized by tranquility, affection, and compassion, thereby strategically contributing to the reduction of divorce rates. This research aims to elucidate the Communication Strategies of Islamic Community Guidance of Garut Regency in Pre-marital Counseling for Couples, focusing on understanding the audience, composing messages, determining methods, and selecting media. The research utilized a descriptive qualitative approach, incorporating data collection techniques such as observation, in-depth interviews, literature review, and documentation. Anwar Arifin's Communication Strategy Theory was applied for data analysis. The findings unveiled a four-phase communication strategy employed by the Bimbingan Masyarakat Islam of Garut Regency: 1) audience understanding through observing community habits, profiling prospective couples, and identifying characteristics; 2) message crafting covering attention, delineating materials for fostering a harmonious family, and generating interest through interactive activities; 3) adopting an informative approach for material delivery while incorporating diverse methods tailored to participants' needs; 4) adapting media choices based on local situations and community conditions, leveraging widely favored social media platforms.